Using Ambient Noise to Image the Northern East African Rift. (25th April 2019) - Chambers, Emma L.; Harmon, Nicholas; Keir, Derek; Rychert, Catherine A.
Abstract: The northern East African Rift (EAR) is a unique location where we observe continental rifting in the Main Ethiopian Rift (MER) transitioning to incipient seafloor spreading in Afar. Here we present a 3‐D absolute shear wave velocity model of the crust and uppermost mantle of the northern EAR generated from ambient noise tomography. We generate 4, 820 station pair correlation functions, from 170 stations (present over 12 years), which were inverted for phase velocity from 8–33 s period and finally for 3‐D absolute shear velocity structure to 60‐km depth. Everywhere in the uppermost mantle, shear velocity is slower than expected for a mantle peridotite composition (<4.1 km/s). This suggests the presence of pervasive partial melt, with focused upwelling and melt storage beneath the MER, where the slowest velocities (3.20 km/s ± 0.03) are observed. Average crustal shear velocity is faster beneath Afar (3.83 km/s ± 0.04) than the MER (3.60 km/s ± 0.04), albeit Afar has localized slow velocities beneath active volcanic centers. We interpret these slow‐velocity regions (including the MER) as magmatic intrusions and heating of the crust. Beneath the northwestern plateau, crustal velocities are laterally heterogeneous (3.3–3.65 ± 0.05 km/s at 10 km), suggesting a complex geological history and inhomogeneous magma distribution during rift development. Comparison between the MER and Afar allows us to draw conclusions between different stages of rifting. In particular, the MER has the slowest crustal velocities, consistent with longer magma residence times in the crust, early during the breakup process. Plain Language Summary: In Ethiopia, the African Continent is rifting apart to slowly form a new ocean basin, which will expand the Red Sea and the Gulf of Aden. How and why this rifting is occurring remains an important unanswered question in earth science. We know tectonic forces are partly responsible, but magmatism also seems a key ingredient for breaking up Africa. Here we use seismic images obtained from signals pulled out of noise, to understand the crustal structure of the region; In particular, how and where magma is stored in the crust, and its relationship to the different stages of continental breakup visible in the region. We find evidence for long‐term melt storage in places where rifting is just beginning in southern Ethiopia; whereas in regions where the crust is thinner due to extensive rifting, magma erupts more regularly. The long‐term storage of magma in unrifted crust may help to heat and weaken it, allowing rifting to accelerate and propagate further south. We are also able to image regions with hydrothermal fluids in the shallow parts of the crust in inactive fault zones. These results provide insight into the breakup process and the role magma plays at different stages of rifting. Key Points: Uppermost mantle velocities are 9% slower than the ak135 model requiring elevated temperatures and fluids; melt percent estimates are 1.1‐2% The Main Ethiopian Rift has the slowest velocities at all depths in this study due to longer melt residence times within the crust Shear velocity is heterogeneous beneath the northwestern plateau suggesting crustal structure, and formation is more complex than thought